Fungal endophytes of Taxus species and regulatory effect of two strains on taxol synthesis - Zhang, Hongshan; Lin, Wanting; Ma, Ruoyun; Zang, Yue; Hou, Kailin; Xu, Zhen; Xi, Xiaoyun; Zhang, Weiting; Tang, Shini; Liang, Xueshuang; Sun, Yiming; Shen, Chenjia (BMC microbiology, 2024)
Taxol, derived from Taxus trees, is a valuable natural resource for the development of anticancer drugs. Endophytic fungi from Taxus trees are a promising alternative source of Taxol. However, the impact of plant-endophytic microbial interaction on the host's Taxol biosynthesis is largely unknown. In the current study, the diversity of endophytic fungi in three different Taxus species was analyzed using Internal Transcribed Spacer sequencing. A total of 271 Operational Taxonomic Units (OTUs) were identified, grouping into 2 phyla, 8 classes, 16 orders, 19 families, and 19 genera. Alpha and beta diversity analysis indicated significant differences in endophytic fungal communities among the various Taxus trees. At the genus level, Alternaria and Davidiella were predominantly found in T. mairei and T. media, respectively. By utilizing a previously published dataset, a Pearson correlation analysis was conducted to predict the taxol biosynthesis-related fungal genera. Following screening, two isolates of Alternaria (L7 and M14) were obtained. Effect of inoculation with Alternaria isolates on the gene expression and metabolite accumulation of T. mairei was determined by transcriptomic and untargeted metabolomic studies. The co-inoculation assay suggests that the two Alternaria isolates may have a negative regulatory effect on taxol biosynthesis by influencing hormone signaling pathways. Our findings will serve as a foundation for advancing the production and utilization of Taxus and will also aid in screening endophytic fungi related to taxol production.